Etiological Evaluation of Hyponatremia in Adult Patients Admitted into a Tertiary Care Hospital in Bangladesh - Pandit, Abhizit; Chakraborty, Dwijaraz; Sristy, Ananya Lahiri; Afroz, Monira; Sakib, Nazmus (Mugda Medical College Journal, 2025)
Hyponatremia, characterized by low sodium levels in the blood, is indeed a common electrolyte disorder, particularly among hospitalized patients. The clinical diagnosis can be challenging due to the varied symptoms it presents, and its etiology can be diverse. A cross-sectional, observational study was conducted in the Department of Medicine, Shaheed Suhrawardy Medical College Hospital, Dhaka, Bangladesh, from September 2016 to March 2017, to evaluate the causes behind hyponatremia in adult patients. A total of 50 patients presented with clinical features and investigation-proven hyponatremia enrolled in this study as the study population purposively. Data was collected in pre-designed data collection sheet. Data compilation, sorting and analysis were conducted using the MS-Excel & SPSS version 22.0. The majority of patients experienced multifactorial etiology for hyponatremia. The most prevalent cause was gastrointestinal loss (20%), followed by chronic renal insufficiency (16%), congestive cardiac failure (12%), cerebrovascular disease (10%), cirrhosis of the liver (10%), meningitis (6%), and thiazide diuretics (6%). Bronchogenic carcinoma and hypothyroidism were identified as the least common contributors to hyponatremia. Our study revealed a statistically significant difference between male and female participants in gastroenteritis causing hyponatremia (p=0.031). Gastrointestinal loss (gastroenteritis), cirrhosis of the liver, and bronchogenic carcinoma were predominant causes in the male population, accounting for 21.2%, 12.1%, and 6.07% respectively. In contrast, chronic renal insufficiency, hypothyroidism, and meningitis were important causes of hyponatremia in the female population, present in 17.6%, 11.7%, and 11.7% respectively. Recognizing the risk factors associated with symptomatic hyponatremia is crucial for devising effective preventive strategies. Mugda Med Coll J. 2024; 7(2): 77-81